Keterlibatan Mahasiswa KKN dalam Kegiatan BKSN untuk Meningkatkan Partisipasi Umat di Paroki St. Fransiskus Asisi Lamahora - Lamak, Benedikstus Igo; Hinga, Dorothea Donge; Nitit, Krisjayanti Walen; Raring, Maria Elisabeth Wesan; Kalang, Prichilia Pega; Lebao, Yohana Antonia Nini; Wathun, Yohanes Maria Vianey Benolo (Abdibaraya, 2025)
Community Service (PKM) activities at St. Francis of Assisi Lamahora Parish were carried out to build congregational participation in church life, especially in BKSN activities. The purpose of this activity is to increase awareness and participation of the congregation in BKSN activities and to improve the quality of life of the congregation at St. Francis of Assisi Lamahora Parish. The method used in the KKN activities at St. Francis of Assisi Lamahora Parish is the live-in approach which emphasizes the active participation of the congregation in every activity. The results of this activity show that the activities carried out at St. Francis of Assisi Lamahora Parish have succeeded in increasing congregational participation in church activities, especially in BKSN activities.